Patching therapy in patients with strabismic amblyopia and refractive amblyopia - Sharanjeet-Kaur,; Waheeda Azwa Hussein,; Norliza Mohd. Fadzil,; Azrin E. Ariffin, (Universiti Kebangsaan Malaysia, 2011)
This study was conducted to compare the treatment outcome using patching in patients with strabismic amblyopia and refractive amblyopia. The treatment outcome was measured by visual acuity and refractive error. A total of 28 patients participated in this study. One group comprised of strabismic amblyopes who had either congenital esotropia or intermittent exotropia and spherical equivalent refractive error of less than -3.00 DS. Another group of patients were purely refractive amblyopes. Patients were first corrected with the best correction for a month. When the VA in the amblyopic eye did not improve over the month, then patching treatment was started. Patching was done daily for 2 h together with near activity. The treatment was carried out for 4 months, with the patients reviewed once every month. The results of the study revealed that VA improved by 17 alphabets or 3 lines after patching treatment for patients with strabismic amblyopia. In the refractive amblyopia group, the VA only improved by 8 alphabets or 1 line 3 alphabets. The mean spherical equivalent refractive error changed by less than -0.50DS and therefore was clinically not significant in both groups. This present study showed that patching treatment was better at improving the VA of patients with strabismic amblyopia.